IMPLEMENTING CURRICULUM 2013 IN ENGLISH LESSON AT SMPN 52 MAKASSAR - Muhammad Iqbal Maliang; Restu Januarty; Rampeng Rampeng (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The objectives of this study were to find out The Implementation teaching learning planning of 2013 curriculum. The research was qualitative method. The sample of the research was English teachers of SMPN 52 Makassar. The data of this research were collected by using triangulation technique by combining observation, interview, and documentation technique. The writer used observation guidelines sheet in analyzing the data collected and monitor. The writer used interview guidelines and recorder to record the interviews. The obtained data was analyzed in three major phases namely data reduction, data display and conclusion. This Result of this study shows that English teachers has already implemented learning the 2013 curriculum in class well. And then, prepare learning tools are in accordance with the standard 2013 curriculum. It can be proved by formation learning tools.